Shining the Lamp: The Rhetoric of 2 Samuel 5-24 - Firth, David G. (Tyndale bulletin, 2001)
2 Samuel 5–24 is here read as a literary unit that covers the whole of the reign of David over Israel and Judah. It is argued that there is an intentional rhetorical pattern that is evident in the literary structure of these chapters, and that the aim of the whole section is to suggest a positive assessment of the whole of David’s reign. This assessment is directed towards the exiles, offering hope because of the continuing validity of the promises to David.